The Analysis of Logic Model Components from Nutrition Care Village Activity to Assist Stunting Reduction in Lamongan District - Dwi Rani Indra Swari; Ratna Dwi Wulandari (Universitas Airlangga, 2022)
Background: The nutrition care village is one of the PELITA program’s activities and has goals for reducing stunting in Lamongan District. As stunting cases in Lamongan District decreased from 15.6% in February 2018 to 7.0% in August 2020, the achievement related to toddler undernutrition has increased from 2016 to 2019, namely 4.73%, 4.10%, 5.26%, and 6.87%. That output can potentially affect the quality of human resources or other problems in the future if it not handled properly. Objectives: Analyze the components of the logic model from nutrition care village activity to assist the stunting reduction in Lamongan District. Methods: This study was quantitative research, using questionnaires and observation methods. Then the data were subjected to descriptive analysis. The research sample was nine community health centers selected by purposive sampling. Results: Logic model components in this study consist of inputs, activities, and outputs. Input factors were facilities and infrastructure, SOPs, and human resources. The facilities and infrastructure were fulfilled by coordinating with the community and stating that they do not yet have SOPs in a written document. The number of nutritionists in inpatient community health centers did not meet the minimum standards. The activities were for stunting areas, so they did not cover all villages. The outputs were 6 out of 9 community health centers reach the wasting target. Conclusions: The results of the analysis were quite good. Some community health centers that did not meet the standard need improvements.